Fabrication and Luminescence of Monolayered Boron Nitride Quantum Dots. Issue 1 (10th July 2013) - Lin, Liangxu; Xu, Yaoxian; Zhang, Shaowei; Ross, Ian M.; Ong, Albert C. M.; Allwood, Dan A.
<x xml:space="preserve">Abstract</x> Monolayered boron nitride (BN) quantum dots (QDs; lateral size ≈10 nm) are fabricated using a novel method. Unlike monolayered BN sheets, these BN QDs exhibit blue‐green luminescence due to defects formed during preparation. This optical behavior adds significant functionality to a material that is already receiving much attention. It is further shown that the QDs are nontoxic to biological cells and well suited to bio‐imaging. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>